PENERAPAN PERMAINAN BOLA KECIL UNTUK MENINGKATKAN KONSENTRASI ANAK SEKOLAH DASAR - Hutasoit, Deviana; Sitinjak, Kezia Nurhayati; Zebua, Hestiayani; Sembiring, Heka Maya Sari Br (PUAN INDONESIA, 2025)
This community service aims to thoroughly explore the impact of using small ball game methods on enhancing students’ motor skills at the HKBP Padang Bulan Educational Foundation. The focus is to analyze the extent to which this method can improve key components of motor skills, such as coordination, agility, and movement accuracy. The approach adopted in this community service consists of two cycles. Each cycle includes planning, implementation, observation, and reflection stages to ensure that the data collected is both relevant and accountable. This initiative involved 15 fifth-grade students as research subjects, representing an age group in primary education that is highly relevant to motor skill development. The findings revealed that the small ball game method significantly improved students’ motor skills. These improvements were observed across various aspects, such as hand-eye coordination, body agility in movement, and accuracy in performing physical tasks. Based on these results, the small ball game method has proven to be an effective and enjoyable approach for implementation in physical education at the elementary school level. It demonstrates a positive contribution to the optimal and continuous development of students’ motor skills.